Bureaucratic recentralisation of Nepal's community forestry sector. (1st December 2019) - Basnyat, B.; Treue, T.; Pokharel, R.K.
This paper explores the forest bureaucracy's practices of implementing community forest policies in Nepal and how this shapes the realities of community forestry for forest user groups. To this end, we conducted a content analysis of community forest management plans; surveyed 74 community forest user groups; conducted intensive field observation in six community forests and interacted with executive committee members and forest bureaucrats from two western hill districts. Our results show that forest user groups were hardly aware of their formal rights, including the obligations of forest bureaucrats to deliver free-of-charge services and technical support. Nobody holds forest bureaucrats accountable for failing to fulfil this part of their official duties. Rather, the forest bureaucrats have established different legal and extralegal processes and mechanisms through which they regain and maintain control over community forest resources. We call this 'bureaucratic recentralisation', and it allows forest bureaucrats to reap personal benefits, including unofficial revenues for delivering statutorily no-cost services.